Pengembangan Sistem Informasi Absensi Digital Berbasis Web pada LKP Al Azka Pringsewu - k, Khaidarmansyah; s, Suwandi (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2025)
Lembaga Pendidikan dan Kursus (LPK) Al Azka Pringsewu is a non-formal educational institution focused on enhancing community skills, particularly in computer education and human resource development. In daily learning activities, student attendance recording is crucial for monitoring discipline and evaluating learning performance. However, the attendance system at LPK Al Azka is still manual, relying on paper-based records that are vulnerable to data loss, damage, and difficulty in data retrieval. Furthermore, the manual recap process is time-consuming and prone to errors and signature manipulations, reducing data accuracy and administrative effectiveness. To address these challenges, this study develops a web-based digital attendance information system utilizing QR Code technology that enables real-time attendance recording automatically stored in a secure database. The system features student data management, attendance session scheduling, live attendance monitoring, and automatic attendance report generation in Excel format, accelerating administrative processes. The implementation of this digital attendance system successfully improves efficiency, accuracy, and data security while supporting transparency and professionalism in attendance management at LPK Al Azka. Accessible via computers and smartphones, this system supports digital transformation in non-formal education and is expected to be a sustainable solution for managing student attendance administration.